BODY DISSATISFACTION AND THE RISK OF EATING DISORDER BEHAVIOR AMONG FEMALE STUDENTS: STUDY CROSS SECTIONAL - Gracia Gisela Viori; Yunita Astriani Hardayati (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Eating behavior encompasses both healthy and unhealthy eating habits (eating disorders) aimed at meeting the body’s nutritional needs through macronutrients and micronutrients. The risk of developing an eating disorder can arise due to physical changes during puberty, cultural factors, social, economic, and nutritional awareness. The purpose of this study is to determine the relationship between high school girls’ body dissatisfaction and their likelihood of engaging in eating disorder behaviors. The BSQ-16A and EAT-26 instruments were used in a quantitative cross-sectional study conducted at Santo Leo II High School from November 18 to November 28, 2024, using Google Forms and obtaining informed consent from 84 participants. Chi-square statistical analysis was then applied to the collected data. According to the findings, 79.8% of participants were not at risk of developing an eating disorder, and 34.5% were not concerned about their body shape. There was a significant correlation between body dissatisfaction and the risk of eating disorder behaviors among high school girls, according to statistical analysis using the chi-square test, with a p-value <0.001. Our study found that among high school girls, body dissatisfaction was significantly correlated with the risk of eating disorder behaviors.